Characterization of endophytic bacteria isolated from wild rice plants in the Mekong Delta, Vietnam - QUACH VAN CAO THI; NGUYEN LU KHOI MINH; NGUYEN PHUONG THUY; TRUONG QUOC TAT; THANH TRAN (Society for Indonesian Biodiversity, 2024)
Abstract. Thi QVC, Minh NLK, Thuy NP, Tat TQ, Tran T. 2024. Characterization of endophytic bacteria isolated from wild rice plants in the Mekong Delta, Vietnam. Biodiversitas 25: 2576-2585. Endophytic bacteria bring many benefits to plants, such as stimulating plant growth and inhibiting many microbial pathogens that cause plant diseases. Hence, this investigation aimed to evaluate the association of endophytic bacteria with wild rice (Oryza rufipogon) that can fix nitrogen, solubilize phosphorus and produce indole-3-acetic acid (IAA). Twelve-five bacterial strains were recovered from wild rice stems and roots collected from Vinh Long and Tien Giang provinces of the Mekong Delta. Among these strains, six had phosphorus solubilizing and seven had nitrogen-fixing activity. Strain BR3.5 fixed the highest nitrogen, i.e. ammonia (NH4+) content of 0.109 ± 0.002 mg/L after eight-day incubation. However, the highest phosphorus solubilization was recorded in two isolates, RR3.7 and RR1.1, with clear zone diameters of 0.800 ± 0.020 mm and 0.800 ± 0.030 mm, respectively. In addition, bacterial strains could synthesize IAA, and BR2.5 produced the highest, i.e., 0.067 ± 0.002 ?g/mL, IAA after eight-day incubation. Notably, strain BR3.5 exhibited multiple activities like nitrogen fixation (0.109 ± 0.002 mg/L), phosphorus solubilization (1.02 ± 0.002 mm), and IAA synthesis (0.056 ± 0.00 ?g/mL). Strain BR3.5 was identified as Pantoea sp. based on 16S rRNA gene sequencing (92.69% similarity) together with morpho-physiological and biochemical characteristics. The findings indicate that strain BR3.5 may be used for the production of biofertilizers for rice farming.